2020
DOI: 10.1038/s41598-020-79405-9
|View full text |Cite
|
Sign up to set email alerts
|

A report on COVID-19 epidemic in Pakistan using SEIR fractional model

Abstract: Recently, novel coronavirus is a serious global issue and having a negative impact on the economy of the whole world. Like other countries, it also effected the economy and people of Pakistan. According to the publicly reported data, the first case of novel corona virus in Pakistan was reported on 27th February 2020. The aim of the present study is to describe the mathematical model and dynamics of COVID-19 in Pakistan. To investigate the spread of coronavirus in Pakistan, we develop the SEIR time fractional m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
42
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 71 publications
(44 citation statements)
references
References 36 publications
0
42
0
2
Order By: Relevance
“…The results of ( Meo et al, 2020 ) revealed a significant decrease in the number of daily new cases and deaths in countries with high temperature and low humidity, compared to those countries with low temperature and high humidity. ( Ahmad et al, 2020 ) to investigate the spread of coronavirus in Pakistan, have develop the SEIR time fractional model with newly, developed fractional operator of Atangana–Baleanu. The result of the study indicated that the spread of virus is very rapidly.…”
Section: Discussionmentioning
confidence: 99%
“…The results of ( Meo et al, 2020 ) revealed a significant decrease in the number of daily new cases and deaths in countries with high temperature and low humidity, compared to those countries with low temperature and high humidity. ( Ahmad et al, 2020 ) to investigate the spread of coronavirus in Pakistan, have develop the SEIR time fractional model with newly, developed fractional operator of Atangana–Baleanu. The result of the study indicated that the spread of virus is very rapidly.…”
Section: Discussionmentioning
confidence: 99%
“…Social network helplines were launched by the government in seven local languages (33). Every medical organization that was supporting the treatment of COVID-19 positive patients was required to conduct "need and availability assessment" of supplies equipment, personal protective equipment (PPE), and laboratory diagnostics, including identification of sources to ensure provision and availability of these (34). Pakistan also observed an uptick in suicidal rates during and after the pandemic, most of these suicides occurring due to a lockdownrelated socioeconomic distress and the fear of infection (34,35).…”
Section: Covid-19 In Vietnam and Pakistanmentioning
confidence: 99%
“…Moreover, Giordano and colleagues [20] developed a new mathematical model based on eight compartments to forecast COVID-19 trend in Italy. Ahmad and colleagues [21] proposed a fractional SEIR model to investigate the spread of the COVID-19 in Pakistan during the first pandemic wave using, also, the next generation matrix algorithm to compute the basic reproduction number R 0 . Kuzdeuov and colleagues [22] developed a COVID-19 simulator for Kazakhistan through a stochastic SEIR model.…”
Section: Introductionmentioning
confidence: 99%